Sexual dimorphism in locomotor performance and its relation to morphology in wall lizards (Podarcis bocagei) - Kaliontzopoulou, A. (2018)
Sexual dimorphism (SD) is the result of evolutionary pressures acting differentially on members of each sex. Investigating the association between SD observed in different sets of phenotypic traits, which are evolutionarily linked, can shed light on the mechanisms causing SD variation within and across species. Although the association between morphology and locomotor performance is a major paradigm in ecomorphology, substantially less effort has been dedicated to investigate the covariation between both sets of traits in the context of sexual divergence. Here, we investigated morphology and locomotor performance in wall lizards Podarcis bocagei to determine if locomotor SD exists in this species, as one may expect based on the morphological SD observed, and test whether both types of SD are directly associated. Our results indicate that signiﬁcant morphological and locomotor SD exists in this species, reporting a signiﬁcant locomotor SD for the ﬁrst time in this genus of lizards. Our study also provides evidence that a direct association between morphology and performance exists at the individual level, binding together SD in both sets of traits. The observed patterns of SD suggest that male locomotor capacity and the corresponding morphological features are well suited for sprinting in level surfaces, but less so for other types of locomotion, potentially as a result of sexual selection acting on male locomotor performance through inﬂuences on territory defence and reproductive ﬁtness.